Elevated gene expression of glutamate receptors in noradrenergic neurons from the locus coeruleus in major depression - Chandley, Michelle J.; Szebeni, Attila; Szebeni, Katalin; Crawford, Jessica D.; Stockmeier, Craig A.; Turecki, Gustavo; Kostrzewa, Richard M.; Ordway, Gregory A. (The international journal of neuropsychopharmacology, 2014)
Glutamate receptors are promising drug targets for the treatment of urgent suicide ideation and chronic major depressive disorder (MDD) that may lead to suicide completion. Antagonists of glutamatergic NMDA receptors reduce depressive symptoms faster than traditional antidepressants, with beneficial effects occurring within hours. Glutamate is the prominent excitatory input to the noradrenergic locus coeruleus (LC). The LC is activated by stress in part through this glutamatergic input. Evidence has accrued demonstrating that the LC may be overactive in MDD, while treatment with traditional antidepressants reduces LC activity. Pathological alterations of both glutamatergic and noradrenergic systems have been observed in depressive disorders, raising the prospect that disrupted glutamate-norepinephrine interactions may be a central component to depression and suicide pathobiology. This study examined the gene expression levels of glutamate receptors in post-mortem noradrenergic LC neurons from subjects with MDD (most died by suicide) and matched psychiatrically normal controls. Gene expression levels of glutamate receptors or receptor subunits were measured in LC neurons collected by laser capture microdissection. MDD subjects exhibited significantly higher expression levels of the NMDA receptor subunit genes, GRIN2B and GRIN2C, and the metabotropic receptor genes, GRM4 and GRM5, in LC neurons. Gene expression levels of these receptors in pyramidal neurons from prefrontal cortex (BA10) did not reveal abnormalities in MDD. These findings implicate disrupted glutamatergic-noradrenergic interactions at the level of the stress-sensitive LC in MDD and suicide, and provide a theoretical mechanism by which glutamate antagonists may exert rapid antidepressant effects.